Patterns and Severity of Injuries in Patients Following Physical Assault– A Medicolegal Aspects - Chaudhary, Archana; Kunwar, Srijana; Ghimire, Samjhana; Wasti, Harihar (Eastern Green Neurosurgery, 2020)
Background and purpose: Physical assault (PA) is a common cause of mortality and morbidity throughout the world and the prevalence is still very high in underdeveloped and developing countries. With the objective to see the spectrum of injury following PA from the medico legal point of view, this study was design in a tertiary care centre at far eastern part of Nepal. Material and method: This is a prospective analytical study with non- probability consecutive sampling of physical assault cases presented in the emergency department over the duration of 4 months. All the patients who meet the inclusion criteria were collected in preformed proforma. Gender, types of weapons used for PA, location of external and internal injuries, various treatment strategies, and severity of injuries were presented in frequencies and percentage. Association of different age categories, gender and types of weapons used with severity of injuries were analysed using Chi square/ Fisher’s exact test wherever applicable. Result: There were total 99 patients presented with physical assault during the study period with mean age of presentation 31.69 (SD 13.38) Years with male (70%) predominance. Among various types of weapons used for PA; punches/ kicks were used in 50% of assaults followed by blunt heavy objects (35%) and sharp heavy weapons (14%). Location of the external injuries were more common in head and neck area . Obvious internal injuries were seen in 14% of the assaulted patients. Among all the case of PA, 42% patients needed some sort of surgical intervention during hospital stay. There were 9% cases of grievous injury and 6% had life threatening injuries. Conclusion: Physical assault is a common mode of injuries in eastern Nepal, where young males are more prone to such injuries. Violence are commonly carried out using fists, kicks and blunt objects. Severity of injuries is similar with all the types of weapons used.